The CARMENES search for exoplanets around M dwarfs: rotational variation in activity indicators of Ross 318, YZ CMi, TYC 3529-1437-1, and EV Lac - Schöfer, Patrick; Jeffers, S. V.; Reiners, A.; Zechmeister, M.; Fuhrmeister, B.; Lafarga, M.; Ribas, I.; Quirrenbach, Andreas; Amado, P. J.; Caballero, J. A.; Anglada-Escudé, G.; Bauer, F. F.; et al. (Astronomy and astrophysics, 2022)
Context. The Calar Alto high-Resolution search for M dwarfs with Exo-earths with Near-infrared and optical Échelle Spectrographs (CARMENES) instrument is searching for periodic radial-velocity (RV) variations of M dwarfs, which are induced by orbiting planets. However, there are other potential sources of such variations, including rotational modulation caused by stellar activity.Aims. We aim to investigate four M dwarfs (Ross 318, YZ CMi, TYC 3529-1437-1, and EV Lac) with different activity levels and spectral sub-types. Our goal is to compare the periodicities seen in 22 activity indicators and the stellar RVs, and to examine their stability over time.Methods. For each star, we calculated generalised Lomb-Scargle periodograms of pseudo-equivalent widths of chromospheric lines, indices of photospheric bands, the differential line width as a measure of the width of the average photospheric absorption line, the RV, the chromatic index that describes the wavelength dependence of the RV, and parameters of the cross-correlation function. We also calculated periodograms for subsets of the data and compared our results to TESS photometry.Results. We find the rotation periods of all four stars to manifest themselves in the RV and photospheric indicators, particularly the TiO 7050 index, whereas the chromospheric lines show clear signals only at lower activity levels. For EV Lac and TYC 3529-1437-1, we find episodes during which indicators vary with the rotation period, and episodes during which they vary with half the rotation period, similarly to photometric light curves.Conclusions. The changing periodicities reflect the evolution of stellar activity features on the stellar surface. We therefore conclude that our results not only emphasise the importance of carefully analysing indicators complementary to the RV in RV surveys, but they also suggest that it is also useful to search for signals in activity indicators in subsets of the dataset, because an activity signal that is present in the RV may not be visible in the activity indicators all the time, in particular for the most active stars.
Gesehen am 25.09.2022